American Founding Son : John Bingham and the Invention of the Fourteenth Amendment - Magliocca, Gerard N. (Book collections on Project MUSE., 2013)
John Bingham was the architect of the rebirth of the United States following the Civil War. A leading antislavery lawyer and congressman from Ohio, Bingham wrote the most important part of the Fourteenth Amendment to the Constitution, which guarantees fundamental rights and equality to all Americans. He was also at the center of two of the greatest trials in history, giving the closing argument in the military prosecution of John Wilkes Booth's co-conspirators for the assassination of Abraham Lincoln and in the impeachment of President Andrew Johnson. And more than any other man, Bingham playe.